Given that lo g 9 x = lo g 1 2 y = lo g 1 6 ( x + y ) , find x y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let all these equal to k . Then, 9 k = x , 1 2 k = y , 1 6 k = ( x + y ) As, 1 6 × 9 = 1 2 2 , ⟹ x ( x + y ) = y 2 Dividing throughout x 2 , x 2 y 2 − x y − 1 = 0 ⟹ x y = 2 1 + 5 = 1 . 6 1 8
lo g 9 x lo g 9 lo g x = lo g 1 2 y = lo g 1 6 ( x + y ) = lo g 1 2 lo g y = lo g 1 6 lo g ( x + y ) Convert to same logarithm base.
⟹ ⎩ ⎪ ⎨ ⎪ ⎧ lo g x lo g y = lo g 9 lo g 1 2 = 2 lo g 3 lo g 3 + lo g 4 = 2 1 + lo g 9 lo g 4 lo g x lo g ( x + y ) = lo g 9 lo g 1 6 = 2 ⋅ lo g 9 lo g 4 . . . ( 1 ) . . . ( 2 )
( 1 ) : lo g x lo g y 2 lo g y lo g y 2 y 2 x y = 2 1 + 2 lo g x lo g ( x + y ) = lo g x + lo g ( x + y ) = lo g ( x ( x + y ) ) = x ( x + y ) = y x + 1 Multiply both sides by 2 lo g x . Divide both sides by x y . Multiply both sides by x y and rearrange.
( x y ) 2 − x y − 1 ⟹ x y = 0 = 2 1 + 5 ≈ 1 . 6 1 8 Solve the quadratic for x y . Note that x y > 0
Do you have to show that both x and y are positive? If x and y were both negative, their quotient would be positive, but the original equation would not be satisfied. Solving for x/y in this manner seems to ignore the constraints on the variables.
Log in to reply
I think it should be specified in the problem.
Problem Loading...
Note Loading...
Set Loading...
Let lo g 9 x = lo g 1 2 y = lo g 1 6 ( x + y ) = α . Then x = 9 α , y = 1 2 α and x + y = 1 6 α .
x = 9 α x + y = 1 6 α ⟹ ⟹ x = 3 α x + y = 4 α x y = 9 α 1 2 α x 2 y 2 x y 2 − x 2 y − x 3 x 2 y 2 − x y − 1 x y = 3 α 4 α = x x + y = x x + y = 0 = 0 = 2 ( 1 ) 1 ± ( - 1 ) 2 − 4 ( 1 ) ( - 1 ) = 2 1 + 5 = ϕ ≈ 1 . 6 1 8 0 3 3 9 8 8 7 5 [We can divide by x 3 since x = 0 ] [We can discard the negative solution as x y > 0 ]